ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Nely Febriana (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The company is a business entity that carries out a production activity in the form of goods or services, which is limited by financial reports, financial statements must be reported on time to maintain the level of relevance because financial reports are the main source used by users of financial statements to obtain information about company performance. used for economic or business decision making. Companies are said to be on time if their financial reports do not exceed the time limit stipulated in the regulations issued by the Capital Market and Financial Statements Supervisory Agency. Manufacturing companies are the most listed companies on the Indonesia Stock Exchange, this study uses an empirical study of manufacturing companies in the goods industry sector. Consumption of 31 companies in the 2015-2019 period will be analyzed for the timeliness of financial reporting. Analysis of these factors using four variables, namely profitability, solvency, liquidity and company size, using the ROA, DAR, CR and Ln Total Asset indicators, using a probability level of 5% or 0.05, The results of this study indicate that profitability does not affect the timeliness of financial reporting, while solvency, liquidity and company size. Keywords: Timeliness, profitability, solvency, liquidity and company size.